PENGGUNAAN MEDIA SOSIAL INSTAGRAM "ZAP" SEBAGAI BISNIS PERAWATAN KULIT DALAM PROMOSI IKLAN DI ERA EKONOMI DIGITAL - Nabilah Rahman Dozan (2022)
This study aims to anayze advertising Instagram social media used by a skin care business called ZAP as a place for advertising and promotioning of ZAP's beauty products and treatments also their their skin care in the digital economy era by connecting with new media theory. The method used is descriptive qualitative with primary and secondary data sources. The sampling technique was purposive sampling technique by taking samples based on the appropriate groups to be used as informants as a complement to reseach the data. The data obtained from in-depth interviews with two sources from ZAP's internal and two sources from ZAP's external as well as focused observations on ZAP's Instagram social media. Researcher used a case study approach to achieve a more in-depth understanding of a case according to the research discussion. The final result of this study shows that the advertising activities used by ZAP in promoting beauty and skin cares products also their treatment on Instagram is using soft-selling and hard-selling advertisements. Soft-selling advertisements are carried out by testimonials from various influencers after doing skin care treatments at ZAP clinic and using ZAP skin care and beauty products as well as providing information about skin care and beauty. Hard-selling ads emphasize the latest promos and boost ads through advertising services provided by Instagram. It should also be noted that the color composition of each content created must match with the brand identity. Messages are written briefly, concisely, and clearly so that the readers easily understood. Images in the content also must match with the message.